Menelaah Dampak Penggabungan Terhadap Profitabilitas PT. Bank Syariah Indonesia - Andika, Sultan (Journal of Principles Management and Business, 2023)
The government's progressive step regarding the policy to merge three Islamic banks is expected to provide a new financial institution alternative for the community and stimulate national economic growth. The purpose of this research is to assess the profitability before and after the merger of Bank Syariah Indonesia, which is the result of the combination of three state-owned banks: Bank Syariah Mandiri, Bank Rakyat Indonesia Syariah, and Bank Negara Indonesia Syariah. This study adopts a quantitative descriptive approach. The author conducts an analysis using a comparative descriptive method, examining profitability ratios such as ROA, ROE, ROI, OPM, and NPM. The data is obtained from financial reports published by Bank Syariah Indonesia. The research results indicate that the average profitability values of Bank Syariah Indonesia show that ROA after the merger is higher than before, reaching 1.19%, and ROE after the merger is also significantly higher, reaching 11.87%. NPM and OPM ratios also experience a remarkable increase from the pre-merger conditions, with NPM soaring to 48.96%, and OPM nearly tripling to 44.54%. However, the ROI value still shows a decrease in percentage compared to the pre-merger period.